Analysis on common problems of the wastewater treatment industry in urban China. (March 2022) - Zhang, Jingbing; Wang, Hongchen; Shao, Yuting; Liu, Guo-hua; Qi, Lu; Dang, Wenyue; Yuan, Junli; Li, Yinghao; Xia, Zhiheng
Abstract: The wastewater treatment industry in urban China generally faces certain common problems. To provide a comprehensive analysis on common problems of the wastewater treatment industry, survey data from 467 wastewater treatment plants (WWTPs) and field investigation reports of 38 WWTPs were analyzed. The research results showed that, the common problems of the wastewater treatment industry are mainly concentrated in WWTPs and the drainage system. The length of per capita drainage networks is insufficient, only 0.85 m; approximately 63.17% WWTPs have hydraulic load rates (HLRs) are greater than 80%, and the ratio of water quality between the design value and actual value is approximately 0.7; and there is still a considerable gap in construction of wastewater treatment facilities compared to those in developed countries. These are still major common problems perplexing the wastewater treatment industry in urban China. In this study, the common problems that hinder improving the operation efficiency of WWTPs were investigated, the causes of the discrepancy were analyzed, and three countermeasures, such as refinement design, optimization facilities and reasonable process control were jointly explored to solve them. This study may provide valuable insights and methods for the wastewater treatment industry to effectively address the discrepancy between the design and actual operation of WWTPs. Graphical abstract: Image 1 Highlights: The current development status of wastewater treatment industry was revisited. Insufficient and backward facilities, irrational design are main common problems. Refinement design is the key link of the efficiency in wastewater treatment. Countermeasures and the prospect of wastewater treatment industry were put forward.